2016
DOI: 10.1039/c6ra03935a
|View full text |Cite
|
Sign up to set email alerts
|

Effective dispersion of aqueous clay suspension using carboxylated nanofibrillated cellulose as dispersant

Abstract: Carboxylated nanofibrillated cellulose extracted from wood fibers was used as a green dispersant to effectively disperse clay particles in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Strong negatively charged COO – groups were introduced to the surface of NFC in this process. Meanwhile, it is known that NFC is an amphiphilic material owing to the presence of hydrophobic C–H moieties and hydrophilic O–H groups on the cellulose molecular chain. , NFC can interact with CNTs through the hydrophobic sites of CNTs and specific crystalline faces (hydrophobic (200) planes) of NFC. As a result, the electrostatic repulsive forces provided by COO – groups and the hydrophobic interaction between NFC and CNTs facilitate the dispersion of CNTs in NFC solution.…”
Section: Resultsmentioning
confidence: 99%
“…Strong negatively charged COO – groups were introduced to the surface of NFC in this process. Meanwhile, it is known that NFC is an amphiphilic material owing to the presence of hydrophobic C–H moieties and hydrophilic O–H groups on the cellulose molecular chain. , NFC can interact with CNTs through the hydrophobic sites of CNTs and specific crystalline faces (hydrophobic (200) planes) of NFC. As a result, the electrostatic repulsive forces provided by COO – groups and the hydrophobic interaction between NFC and CNTs facilitate the dispersion of CNTs in NFC solution.…”
Section: Resultsmentioning
confidence: 99%
“…The TCF is related to the apparent hydrodynamic radius (particle diffusivity), which suggests that HCNFs adsorb onto the bentonite particles (Ferse et al 2008). Indeed, previous work has shown that cellulose nanoparticles and cellulose-based polymers can be used to disperse clays in water (Ming et al 2016;Sjöberg et al 1999). Figure 8 shows a schematic illustration of the interactions and shear-dependent microstructure of composite dispersions of CNF and bentonite or sepiolite.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, it has been shown that CNF-bentonite dispersions display properties suitable for use as drilling fluids (Li et al 2015). However, comprehensive studies on the steady-shear and viscoelastic properties of such CNF-nanoclay dispersions are rare, and previous rheological studies have mainly focused on dispersions of plate-like nanoclays and moderately charged or uncharged nanocellulose particles (Abend and Lagaly 2000;Li et al 2015;Ming et al 2016;Nechyporchuk et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A drop of the cellulose fiber suspension after bleaching was placed on a glass slide for imaging with an optical microscope (OLYMPUS BX51). A drop of CNC suspension was placed on a piece of freshly cleaved mica, dried and then analyzed with Atomic Force Microscope (AFM, Nanoscope IIIa Multimode 8, Bruker) 42 . Lengths and diameters were obtained using the section analysis tool of the NanoScope Analysis software (Bruker, version 1.40) from height mode AFM image.…”
Section: Methodsmentioning
confidence: 99%